(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
The present study aims at clarifying the relationship between the leadership styles of the trainers and their relationship to the cohesion of the sports team - the Quan Khi Dao team is a model - taking into account the types of leadership and their forms and their impact on the cohesion of the group to verify the objectives of the study. The study was based on a sample that was selected in a non-random way with a goal of 20 players and 5 trainers Of the Quan Khi Dao team - a senior category –in hassi Bahbah, and the results showed after analyzing the program spss as: There are no statistically significant differences between the leadership styles of Quan Khi Dao. trainers due to the variable level of education.- There were no statistically significant differences in the cohesion of the Quan Khi Dao team due to the variable of experience. - The leadership styles of trainers do not influence the cohesion of the sports team. Keywords: leadership, cohesion, group, team, sport, Quan Khi Dao.